Time-Consistent Fiscal Policy in a Debt Crisis - Neele Balke; Morten Ravn (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The financial crisis led to severe crises in much of Southern Europe that generated deep economic problems that still have not been resolved. Many of these economies (Greece, Italy, Spain and Portugal) witnessed not only large drops in aggregate activity but also rising levels of debt and falling debt prices which made financing of deficits very costly and triggered concerns about sovereign defaults. A large literature has considered environments in which large negative shocks can generate risk of default because sovereign governments lack commitment to debt. However, much of this literature either assumes that government has commitment to all other fiscal instruments or that these are exogenously determined. Therefore, it is unclear whether adjustments of other instruments - for example cuts in public spending or tax hikes - may not be preferable to default. Moreover, this literature typically does not allow for feedback from the fiscal instruments to the state of the economy beyond those triggered by punishment mechanisms in case of a sovereign default. Thus, these models are not useful for understanding richer questions regarding the adjustment of fiscal policy in crisis times. This paper takes a first step in addressing these issues. We study a small open economy model in which a benevolent government aims at maximizing social welfare but lacks commitment to all its fiscal instruments. The economy consists of a government, households, firms and foreign lenders. Households derive utility from consumption of private goods, leisure and from government provided public goods. They differ in their labor market status because of matching frictions. Some households work and earn labor income. The government imposes a payroll tax on these households. Other households are unemployed but choose search effort. Households cannot purchase unemployment insurance contracts but receive government financed unemployment transfers. Firms post vacancies to hire workers and there is free entry. There is an aggregate productivity shock and wages are determined by a non-cooperative Nash bargaining game between firms and households. The government chooses payroll taxes, unemployment benefits, government spending and may be able to smooth the budget by international borrowing and lending. International lenders are risk neutral and charge an interest rate which takes into account that governments may choose to default. If a government defaults it is excluded from international financial markets for a stochastic number of periods and it may suffer a loss of productivity whilst excluded from international lending. The government in this economy faces several trade-offs. It would like to insure households against unemployment risk and against wage risk which occurs due to productivity shocks. However, more generous unemployment insurance gives households less incentive to search for jobs and therefore produces higher unemployment and a smaller tax base. In order to smooth employed households against wage risk, the government would like to cut payroll taxes when productivity falls but this implies rising debt. The government also attempts to equalize the marginal utility of private and public consumption but cannot do so perfectly because of household heterogeneity. In this economy, falling productivity produces difficult choices since it puts a pressure on the government budget due to rising unemployment and a smaller tax base which produces an incentive for increasing government borrowing. However, rising debt levels may eventually impact on the price of debt because lenders perceive a risk of a sovereign default. For that reason, the government will eventually have to make a hard choice about whether to default on its debt which means it will have to balance its budget (and possibly suffer a drop in productivity), cut unemployment transfers which harms the unemployed, increase payroll taxes which harms the employed and produces higher unemployment, or cut government spending which lowers utility of households. We derive optimal fiscal policies in this environment by studying Markov perfect equilibria. The model is calibrated to emulate the conditions of a typical Southern European economy. We show that the time-consistent policies involve countercyclical payroll taxes, constant unemployment benefits, and mildly procyclical government spending in normal times when the risk of default is negligible. In crisis times, the government is willing to further distort the economy by providing less insurance against unemployment, increasing payroll taxes and cutting public goods provision to limit rising debt. However, once a default becomes inevitable, the government partially lifts such austerity measures since it ceases to be concerned about honouring its outstanding debt.
Keywords: E62; F34; J64; 330